2021
DOI: 10.1021/jacs.1c01471
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Diels–Alder Reactions of gem-Diborylalkenes: Toward the Synthesis of gem-Diboron-Based Polymers

Abstract: Although gem -diborylalkenes are known to be among the most valuable reagents in modern organic synthesis, providing a rapid access to a wide array of transformations, including the construction of C–C and C-heteroatom bonds, their use as dienophile-reactive groups has been rare. Herein we report the Diels–Alder (DA) reaction of (unsymmetrical) gem -diborylalkenes. These reactions provide a general and efficient method for the stereoselective conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…For example, they participate in [4 + 2], [3 + 2], and [2 + 2] cycloadditions, under both thermal and photochemical conditions. In addition, the Diels–Alder (DA) reactions of unsaturated boron compounds have been explored for many decades. , Early reports described the reactions of vinyl- and ethynylboronic esters, which were later extended to a wide variety of boron-substituted dienophiles and dienes. However, although allenylboron compounds have been used in many organic reactions, , including propargylations and allenylations and Suzuki cross-couplings and related reactions, curiously, the potential in cycloaddition reactions has not been disclosed.…”
mentioning
confidence: 99%
“…For example, they participate in [4 + 2], [3 + 2], and [2 + 2] cycloadditions, under both thermal and photochemical conditions. In addition, the Diels–Alder (DA) reactions of unsaturated boron compounds have been explored for many decades. , Early reports described the reactions of vinyl- and ethynylboronic esters, which were later extended to a wide variety of boron-substituted dienophiles and dienes. However, although allenylboron compounds have been used in many organic reactions, , including propargylations and allenylations and Suzuki cross-couplings and related reactions, curiously, the potential in cycloaddition reactions has not been disclosed.…”
mentioning
confidence: 99%
“…To study the vulcanization process of styrene-butadiene rubber (SBR) activated by ZDMC, this work used the DFT method to calculate all stationary points along reaction pathways at the ωB97X-D/BSII//ωB97X-D/BSI level using the Gaussian09 program. BSI denotes the LANL2DZ basis set for Zn and 6-31G­(d) basis set for other atoms, and BSII denotes the LANL2DZ basis set for Zn and 6-31++G­(d,p) basis set for other atoms. Unless otherwise specified, all energies discussed in the following sections are Gibbs free energies calculated at 298.15 K. All stationary points have been confirmed by frequency analysis, and all transition states have been verified with one and only one imaginary frequency. The MCV method was used to choose 3-ethyl-pentene as the simplified model of the SBR single-chain (see Figure S1 of Supporting Information).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Despite these milestone achievements, most reports have mainly focused on the development of a single-step reaction by employing mono-organoboron compounds (Figure a). While these step-by-step sequences are well-tailored for target-oriented synthesis, recent advances have shown that modular and chemoselective transformations of poly­(organoborons), consisting of two or more boron groups on the same molecule, can be an efficient strategy for the rapid and diverse synthesis of molecules with higher complexity (Figure b) . Pioneering works by Burke and Suginome demonstrated that the boron-masking/unmasking strategy enables consecutive C–C bond formation reactions of poly­(organoborons) via palladium-catalyzed Suzuki–Miyaura cross-coupling (SMC), although this approach is only applicable to poly­(organoborons) bearing boron groups at sp 2 -hybridized carbon centers.…”
Section: Introductionmentioning
confidence: 99%